The Effectiveness of Leadership in Enhancing Employee Creativity in Higher Education Institutions is Examined, with Intrinsic and Extrinsic Motivation Identified as Mediators - Angelina Sofya Friscila (Jurnal Manajemen Sains dan Organisasi, 2025)
Objective- In the education service sector such as universities, employee service and performance are highly expected to improve organizational performance. However, working in the traditional way as usual has become a challenge. therefore, employees are required to be more creative in carrying out and completing their work. This research aims to examine the role of transformational leadership style and visionary leadership style in enhancing employee creativity at work, with intrinsic motivation and extrinsic motivation as mediators. Design/Methodology/Approach—The research uses a quantitative method with Smart PLS to test the research hypothesis. With 157 respondents willing to fill out the questionnaire online. To measure the mediation effect, the Upsilon (v) method was used.Findings— The findings indicate that intrinsic motivation and extrinsic motivation can mediate the influence of visionary leadership on employee creativity. Meanwhile, transformational leadership has not yet been able to directly increase motivation. For a more detailed explanation, please refer to the findings and discussion. Conclusion and Implications—Visionary leadership should be used by college management to enhance employee motivation as well as creativity, focusing on organizational vision during training. The organizational environment should encourage intrinsic motivation through visionary leadership and practices such as more autonomy and appreciation of employees to improve creativity.Tis research provides evidence showing visionary leadership to be necessary in creating intrinsic as well as extrinsic motivation among university staff, which in turn results in increased creativity. Intrinsic motivation is found to be the strongest mediator in the relationship between visionary leadership and staff creativity, with a moderate mediating effect